Fermentation Booster Oven to Increase Tape Production In Gambut District, Banjar Regency, South Kalimantan - Irfan, Irfan; Karim, Saiful; Cahyanto, Dwi; Amin, Ahmadil; Mu'ammar, Rais (Institut Teknologi Nasional, Bandung, 2024)
The fermentation process contains the addition of microorganisms to make sticky rice into the desired product. The microorganisms used are yeast. The fermentation process takes quite a long time, making tape production take longer. This community service program aims to increase the productivity of sticky rice tape using a fermentation booster oven. This activity was carried out in Pematang village, sub-district. Gambut district. Banjar, South Kalimantan from April 3 2023 to September 15 2023. The program selection was based on considerations regarding the potential of Pematang village as a center for tape production in the sub-district area. Gambut district. Banjar, South Kalimantan. This Oven Booster tape technology was created with the aim of developing innovation and increasing the productivity of the potential tape business in Pematang village. This activity was carried out by discussing the tape making process and introducing Oven Booster tape technology. The use of this technology received a positive response from the target audience, especially regarding the potential for increasing productivity and quality of tape production.